2008
DOI: 10.1074/jbc.m804067200
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Binding Mechanism of the Macrophage Galactose-type C-type Lectin 1 Revealed by Saturation Transfer Experiments

Abstract: Macrophage galactose-type C-type lectins 1 and 2 (MGL1/2) are expressed on the surfaces of macrophages and immature dendritic cells. Despite the high similarity between the primary sequences of MGL1 and MGL2, they display different ligand specificities. MGL1 shows high affinity for the Lewis X trisaccharide, whereas MGL2 shows affinity for N-acetylgalactosamine. To elucidate the structural basis for the ligand specificities of the MGLs, we performed NMR analyses of the MGL1-Lewis X complex. To identify the Lew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…To elucidate the identity of other basic amino acids involved in binding CS444, we used perdeuterated CCL5 and unlabeled CS444 to carry out a cross saturation experiment, a technique that has been successfully used to identify carbohydrate binding residues in a previous study (Sakakura et al, 2008). The data revealed that the backbone amide proton of S1, Y3 and R17 are significantly perturbed by saturation of CS444 protons (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the identity of other basic amino acids involved in binding CS444, we used perdeuterated CCL5 and unlabeled CS444 to carry out a cross saturation experiment, a technique that has been successfully used to identify carbohydrate binding residues in a previous study (Sakakura et al, 2008). The data revealed that the backbone amide proton of S1, Y3 and R17 are significantly perturbed by saturation of CS444 protons (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…We constructed recombinant MGL-Fc proteins, consisting of the extracellular domains of MGL long and MGL short fused to the human IgG1-Fc domain for detection. Previously, Ala 89 and Thr 111 (Ala 256 and Thr 278 in the full-length MGL1) were shown to be crucial for the Lewis X preference of murine MGL1 (16). Based on these findings and our previous work using the MGL short splice variant (8), we mutated human MGL short at the corresponding amino acids (H259T and K237A) to elucidate whether these amino acids also contribute to the fine specificity of human MGL (Fig.…”
Section: Carbohydrate Recognition Profiles Of Mgl Variantsmentioning
confidence: 87%
“…MGL1 mainly interacts with Lewis X (Gal␤1-4(Fuc␣1-3)GlcNAc) and Lewis A (Gal␤1-3(Fuc␣1-4)GlcNAc) (15), whereas MGL2 recognizes terminal ␣-/␤-GalNAc ((sialyl)Tn antigen, LDN), as well as the terminal galactose in the core 1/T antigen and core 2 O-glycan structures (15). These disparities in ligand recognition have been further elucidated by Sakakura et al (16), showing that whereas the galactose moiety of Lewis X is engaged by the QPD motif in the MGL1 CRD, the fucose residue is bound by a secondary binding site composed of Ala 89 and Thr 111 (corresponding to Ala 256 and Thr 278 in the full-length MGL1; Fig. 1A).…”
Section: The Human Macrophage Galactose-type Lectin (Mgl) Is a C-typementioning
confidence: 93%
See 1 more Smart Citation
“…TDPC protons were selectively irradiated in continuous wave mode for 2 sec and the amide proton signals of the protein were detected by the TROSY pulse scheme following the irradiation (Sakakura et al, 2008). The delay for relaxation between scans was set to 2 sec.…”
Section: Methodsmentioning
confidence: 99%